2017
DOI: 10.3892/etm.2017.4406
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical characteristics of bacterial endophthalmitis in retinopathy of prematurity after intravitreal bevacizumab injection: A case report

Abstract: Abstract. Intravitreal bevacizumab injection (IVB) is emerging as a safe and effective therapy for retinopathy of prematurity (ROP); however, follow-up investigations after IVB have indicated that endophthalmitis, a rare and devastating complication, may develop. The present study reports a case of an infant with ROP who developed endophthalmitis after IVB infection. The infant was administered with an intravitreal injection of broad-spectrum antibiotics to treat the endophthalmitis. A favorable anatomic outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, several studies have shown systemic suppression of VEGF and other growth factors after intravitreal anti-VEGF injection in neonatal infants [1314], raising concerns about neurological or developmental delay [15]. There have also been isolated reports of retinal detachment [161718] and endophthalmitis [19] following intravitreal injections.…”
mentioning
confidence: 99%
“…However, several studies have shown systemic suppression of VEGF and other growth factors after intravitreal anti-VEGF injection in neonatal infants [1314], raising concerns about neurological or developmental delay [15]. There have also been isolated reports of retinal detachment [161718] and endophthalmitis [19] following intravitreal injections.…”
mentioning
confidence: 99%
“…Wang and Xiang used one-third of adult dosage in their case based on the approximation that a premature infant's eye is one-third of the volume of an adult eye. [3] Similar to Ranibizumab dosage, half of the adult dosage was used in our case (0.5 mg vancomycin, 1 mg ceftazidime, and 200 μg dexamethasone).…”
Section: Discussionmentioning
confidence: 99%
“…[2] To the best of our knowledge, only a single report exists on infectious endophthalmitis after anti-VEGF injection in ROP, which described the early clinical characteristics and benefit of early intravitreal antibiotic injection. [3] We here report the course of disease in a case of post-ranibizumab injection endophthalmitis in aggressive posterior ROP (APROP) disease and discuss the management approach.…”
mentioning
confidence: 99%
“…Retinopathy of prematurity (ROP) is a vascular proliferative, blindness-causing disease, and has become one of the worldwide causes of childhood blindness [1]- [5]. ROP is one of the most dangerous and serious complications of premature infants' eyes [6], which can be better prevented in countries with high or middle income.…”
Section: Introductionmentioning
confidence: 99%